Practice of Administrative and Territorial Reform in the EU and Ukraine: Regulatory and Management - Onyshchuk, Svitlana V.; Onyshchuk, Igor I.; Siryk, Zinoviy O.; Turenko, Vitali Ye. (IAEME Publication, 2020)
EN: The purpose of this article is to study the practice of administrative and territorial reform in the European Union in the context of the reform of the administrative and territorial structure in Ukraine in order to deepen the European integration processes and approach the legal standards of the EU countries. During the research, methods of interdisciplinary approach, system analysis, socio-cultural method, social-activity and concrete- historical approach were applied. The article concludes that based on the European experience, the author considers it important to warn domestic reformers that market principles in the public administration system have certain limits of application as a result of intensive implementation of market management principles and deconcentration of management, the public service may become more disjointed and less manageable, which will contribute to the distortion of its public purpose, distancing citizens from state institutions. In the course of the study, it was possible to identify some of the most important common causes of European reforms that affected the peculiarities of the process of reforming the administrative and territorial structure in these countries. Innovative principles and technologies of advanced administrative reforms gradually evolved from the "new state management" to the "good governance" model. the article highlights the formation of the European "framework model" of administrative and state reform. The article analyzes models of successful administrative and territorial reform in a number of advanced European countries.

UK: Метою цієї статті є вивчення практики адміністративно-територіального характеру реформ в Європейському Союзі в контексті реформи адміністративного та територіального устрою в Україні з метою поглиблення євроінтеграційних процесів та наблизитись до правових стандартів країн ЄС. У статті робиться висновок, що на основі Європейського досвіду, автор вважає важливим попередити вітчизняних реформаторів, що ринкові принципи в системі державного управління мають певні межі застосування в результаті інтенсивного впровадження принципів управління ринком.
Практика адміністративної та територіальної реформи в ЄС та Україні : регулювання і управління
Z. Siryk: ORCID 0000-0001-9886-1068
Keywords: local self-government; administrative and territorial reform; budgetary decentralization; financial support; territorial community; local budget; Inter-budgetary relations; місцеве самоврядування; адміністративна та територіальна реформа; бюджет; децентралізація; фінансова підтримка; територіальна громада; місцевий бюджет; бюджетні відносини; КФД (ЛФ)